Ripple's effect - Achor, Shawn; Blankson, Amy.; Rebora, Cecilia (Belvedere, CA : Little Pickle Press, 2012)
The residents of an aquarium learn that often a smile can turn a bully into a friend.
Keywords: Bullying -- Juvenile fiction; Bullies and bullying -- Fiction